Productos agroalimentarios de calidad y turismo en España: Estrategias para el desarrollo local - Gómez Martín, María Belén; Armesto López, Xosé A. (Geographicalia, 2016)
This article shows the relations between the tourism, and the features of an agrarian production based in traditional products, revalued in the last times due to the guarantees of origin. The food and agriculture products take shape, in this context, as a gastronomic tourists resources that make possible the development of tourism and, at the same time, the tourism turns into a promotional and marketing tool of the quality food and agriculture products. Both circumstances join forces with a common objective: the local development of territories traditionally considered as marginal in the regional context.